HUBUNGAN KETERAMPILAN MENYIMAK CERITA RAKYAT TERHADAP KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS VII - yulia zani; Rasdawita; Siti Enik Mukhoiyaroh Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between the listening skills of folk tales and the narrative writing skills of seventh-grade students at MTsN 6 Kota Jambi. Listening and writing are interconnected language skills, where listening as a receptive skill can strengthen writing as a productive skill. This research employed a quantitative approach with a correlational design. Data were collected using two types of tests: an objective test to assess listening skills and a performance-based test to assess narrative writing skills. Data analysis was performed using SPSS version 25. The results of the Spearman correlation test showed a correlation coefficient of 0.454 with a significance value of 0.017 (< 0.05), indicating a significant and positive relationship between listening skills in folk tales and narrative writing skills. These findings suggest that the better students' listening skills, the better their writing performance. Keywords: listening skills, writing skills, folk tales, narrative text, correlation